2011
DOI: 10.1056/nejmoa1109016
|View full text |Cite
|
Sign up to set email alerts
|

SF3B1and Other Novel Cancer Genes in Chronic Lymphocytic Leukemia

Abstract: Background The somatic genetic basis of chronic lymphocytic leukemia, a common and clinically heterogeneous leukemia occurring in adults, remains poorly understood. Methods We obtained DNA samples from leukemia cells in 91 patients with chronic lymphocytic leukemia and performed massively parallel sequencing of 88 whole exomes and whole genomes, together with sequencing of matched germline DNA, to characterize the spectrum of somatic mutations in this disease. Results Nine genes that are mutated at signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
1,025
8
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,005 publications
(1,087 citation statements)
references
References 35 publications
(61 reference statements)
35
1,025
8
19
Order By: Relevance
“…Probes targeting all coding exons or hotspot regions of 27 known CLL driver genes and/or genes previously reported in EGR2-mutated CLL 19,29,[37][38][39][40][41][42][43][44] were designed using Agilent"s SureDesign service (https://earray.chem.agilent.com/suredesign/home.htm, Supplemental Table S4). …”
Section: Analysis Of Concurrent Mutations By Targeted Deep-sequencingmentioning
confidence: 99%
“…Probes targeting all coding exons or hotspot regions of 27 known CLL driver genes and/or genes previously reported in EGR2-mutated CLL 19,29,[37][38][39][40][41][42][43][44] were designed using Agilent"s SureDesign service (https://earray.chem.agilent.com/suredesign/home.htm, Supplemental Table S4). …”
Section: Analysis Of Concurrent Mutations By Targeted Deep-sequencingmentioning
confidence: 99%
“…MSI2 has been shown to regulate normal hematopoiesis and promote aggressive chronic myeloid leukemia [9]. Interestingly, mutations in splicing machinery genes were recently reported as common events in CLL [10], although the correlation between these mutations and subset-specific gene splice-variants requires further investigation.For the next step, we explored ncRNA expression and found that 109 transcripts of previously annotated RNA (suggested or confirmed) were differentially expressed between subset #1 and #4 (Supporting Information Table 5S). Two such examples, SNORD48 ( Fig.…”
mentioning
confidence: 99%
“…While the ultimate technologies to be utilized remain to be established, as discussed by E Campo in this journal, 33 many discoveries are being made, particularly as whole genome/exome sequencing is being explored by many. [33][34][35][36][37] While for some entities, such as chronic lymphocytic leukemia, the mutations being discovered are each present in a relatively small proportion of cases, they may still be of great biological and clinical interest with therapeutic implications. 33,[35][36][37] Detection of other mutations may be useful for diagnostic purposes, being present in a high proportion of a specific type of lymphoid neoplasm.…”
Section: Molecular Studiesmentioning
confidence: 99%
“…[33][34][35][36][37] While for some entities, such as chronic lymphocytic leukemia, the mutations being discovered are each present in a relatively small proportion of cases, they may still be of great biological and clinical interest with therapeutic implications. 33,[35][36][37] Detection of other mutations may be useful for diagnostic purposes, being present in a high proportion of a specific type of lymphoid neoplasm. For example, it has been learned only recently that hairy cell leukemia but very few other B-cell neoplasms have BRAF V600E mutations.…”
Section: Molecular Studiesmentioning
confidence: 99%